2023
DOI: 10.1002/cb.2235
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeat purchase information in electronic word‐of‐mouth (eWOM) on purchase intention

Shang Li,
Jie Chen,
Yiwen Chen

Abstract: Consumers commonly rely on electronic word‐of‐mouth (eWOM) to inform their purchase decisions. The purpose of this study is to investigate when and why repeat purchase information in eWOM influenced customers' purchase behavior, using the social learning theory as a framework. Three experiments were conducted to test the hypotheses. The results showed that repeat purchase information in eWOM positively affected consumers' purchase intention through perceived diagnosticity of eWOM and perceived value. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 97 publications
(196 reference statements)
0
1
0
Order By: Relevance
“…Many studies in consumer behaviour have demonstrated that recommendations coming from friends, in particular, are likely to influence consumer decisions (see, e.g., Chu and Kim, 2011 and See-To and Ho, 2014). Consumers typically regard these personal recommendations as trustworthy, with the trust stemming from the recommendation source's social ties as friends are perceived to have no vested interest in promoting a product, whereas experts and, particularly, companies are perceived to be biased or to have ulterior motives (Cheung et al, 2008;Li et al, 2018). According to a study by Chen et al (2011), consumers are more likely to share and respond to online WOM from friends (vs. strangers or experts) because it aligns with their social connections and dependencies.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Many studies in consumer behaviour have demonstrated that recommendations coming from friends, in particular, are likely to influence consumer decisions (see, e.g., Chu and Kim, 2011 and See-To and Ho, 2014). Consumers typically regard these personal recommendations as trustworthy, with the trust stemming from the recommendation source's social ties as friends are perceived to have no vested interest in promoting a product, whereas experts and, particularly, companies are perceived to be biased or to have ulterior motives (Cheung et al, 2008;Li et al, 2018). According to a study by Chen et al (2011), consumers are more likely to share and respond to online WOM from friends (vs. strangers or experts) because it aligns with their social connections and dependencies.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%